2007
DOI: 10.1002/chin.200724098
|View full text |Cite
|
Sign up to set email alerts
|

Selective Palladium‐Catalyzed ipso Arylation of α,α‐Disubstituted Benzo[b]thien‐2‐ylmethanols with Aryl Bromides Using PCy3 as Ligand.

Abstract: Selective Palladium-Catalyzed ipso Arylation of α,α-Disubstituted Benzo[b]thien-2-ylmethanols with Aryl Bromides Using PCy 3 as Ligand. -The reaction of substrate (I) affords 2-aryl(heteroaryl)benzothiophenes in good to excellent yields. Under the same conditions, benzothien-3-ylmethanol (IV) gives 3-aryl-substituted analogues in poor to good yields. In most cases 2,3-diaryl-substituted benzothiophenes are also formed. 2-Fluorophenyl bromide (IIe) provides exclusively the diarylated product. - (BIRO, A. B.; KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Thus the aryl ring that tends to break the C–C bond will approach the Pd atom to construct axial chirality. Third, the reaction prefers to break the C–C bond attached to the thiophene ring, which has been confirmed in previous studies. ,, …”
supporting
confidence: 78%
“…Thus the aryl ring that tends to break the C–C bond will approach the Pd atom to construct axial chirality. Third, the reaction prefers to break the C–C bond attached to the thiophene ring, which has been confirmed in previous studies. ,, …”
supporting
confidence: 78%
“…As displayed in TS1 and TS2 , axial chirality will be built during the process of the aryl ring approaching the Pd atom. Since the carbon–carbon bond connected to the thiophene ring is more favored to be cleaved than the one connected to the phenyl ring, the process through intermediate Int16 is significantly faster than that through intermediate Int15 . Thus, the kinetic resolution of (±)- 30a can be realized.…”
Section: Asymmetric Ring-opening Through C–c Bond Cleavagementioning
confidence: 99%
“…To prevent such regioselectivity issues, an alternative approach to direct arylation for the formation of aryl–aryl bonds is the cleavage of aryl–carbon bonds. Bilodeau and Forgione reported a palladium-catalyzed cross-coupling of heteroaryl carboxylic acids and aryl halides that was believed to proceed through the β-carbon elimination of CO 2 (Scheme :1). Likewise, Miura et al reported that α,α-disubstituted arylmethanols in the presence of palladium could undergo β-carbon elimination to yield a ketone and an aryl-palladium species that could then be coupled with various aryl halides (Scheme :2). These types of aryl cross-couplings have since been dubbed ipso -arylations and have subsequently been used in a handful of other notable examples. Both methods have been used as an alternative to traditional organometallic cross-coupling methods in the synthesis of conjugated polymers. , …”
Section: Introductionmentioning
confidence: 99%